Surveillance of Antibiotic Resistant Klebsiella pneumoniae in Tertiary Care Hospital of Nepal - Amatya, Niroj Man; Shrestha, Sanjit; Dangal, Laxmi; Paudel, Aarati; Banjara, Sanju; Chaudhary, Sweta (Journal of College of Medical Sciences-Nepal, 2024)
Background Klebsiella pneumoniae is a ubiquitous Gram-negative, non-motile, encapsulated bacterium that resides in the mucosal surfaces of mammals and the environment such as soil, water, etc. Clinically, it is also associated with many infections and conditions that are aggravated by the acquisition of multidrug-resistant genes. Methods This descriptive study was conducted to find out the incidence of Klebsiella pneumoniae in different clinical samples and their antibiotic susceptibility pattern at B & B Hospital, Lalitpur from 12 June 2022 to 11 September 2022. The samples were cultured on MacConkey agar, and standard microbiological techniques were used to confirm the presence of K. pneumoniae. Antimicrobial susceptibility tests were performed using the Kirby-Bauer Disk Diffusion method. Results Of the 1967 different clinical samples, culture positivity was observed in 361 samples. Among these, total number of Klebsiella pneumoniae was 150 (41.55%) and from the urine samples exclusively, 63 (42%) Klebsiella pneumoniae were isolated. The most susceptible and resistant antibiotics were gentamicin and ciprofloxacin respectively. Among the isolates, 85 (56.66%) isolates were multi-drug resistant in which 69 (87.34%) isolates were resistant to carbapenem. Conclusions The diversified infections with a growing number of multi-drug resistant Klebsiella pneumoniae present a major public health concern. The limited availability of effective antibiotics emphasizes the prudent use of available antibiotics and the importance of regular national-wide surveillance of multi-drug resistance patterns.